Microwave Transparent Catalytic Falling‐Film Microreactor for Automated Operation. Issue 2 (3rd January 2019) - Krtschil, Ulrich; Löb, Patrick; Schütt, Christian; Zapf, Ralf; James, Rachel; Bonrath, Werner; Medlock, Jonathan
Abstract: Falling‐film microreactors at different scales were developed to study heterogeneously catalyzed gas‐liquid reactions under microwave irradiation, as part of the EU FP7 project MAPSYN. At pilot scale, this device formed the core part of a fully automated demonstration plant which was used for semi‐hydrogenation reactions at an industrial site. The microchannels of the reaction plate were coated with novel selective catalysts. A special fiber‐optical sensor applicable under microwave irradiation and needed for controlling the liquid level in the sump via the flow rate of the discharge pump was developed and electrically connected with the automation system. Abstract : In the light of the electrification of chemistry and the intended increasing use of renewable resources, a microwave‐transparent catalytic falling‐film microreactor was successfully developed within the EU research project MAPSYN. The glass ceramic MACOR® was used for the microstructured thin reaction plate. The microchannels of the reaction plate were coated with novel selective catalysts.